The spermatozoa ultrastructure of the giant Amazon pirarucu Arapaima gigas (Schinz, 1822). - KIRSCHNIK, L. N. G. (2022)
In this study we provide a first complete ultrastructure description of the spermatozoa from pirarucu A. gigas collected in vivo. To do so, adult male broodstocks of A. gigas held at Embrapa Fisheries and Aquaculture (Palmas-TO, Brazil) were handled for sperm collection.